Uncommon cause of cardiac tamponade in a young man. Issue 1 (20th January 2021) - Narayan, Ananthu; Ojha, Vineeta; Arava, Sudheer; Ray, Animesh
Abstract : We report a rare case of cardiac angiosarcoma in a young boy who presented with cardiac tamponade. His initial symptoms were non-specific. He was initially being managed in the line of fungal infection, with a possibility of malignancy. Cardiac imaging was also not conclusive and he worsened on antibiotics and antifungals and succumbed to the illness. After his death tissue biopsy from heart and lung was done and histopathological examination revealed the diagnosis of metastatic angiosarcoma. The case highlights the importance of considering the diagnosis of cardiac angiosarcoma in the patients presenting with haemorrhagic pericardial effusion and non-specific symptoms.